Conditional analysis of elite beach handball according to specific playing position through assessment with GPS - Zapardiel, J. C.; Asin-Izquierdo, I. (International Journal of Performance Analysis in Sport, 2020)
Beach handball needs to continue to develop. For this reason, observational studies that analyse competitive demands are necessary. Therefore, our objective in this work was to carry out performance assessment of the beach handball players regarding specific playing positions during competition, without modifying the specific structure of the game. The study included 57 elite beach handball players. The results showed that significant differences were found in most of the variables studied when the specific playing positions were compared. Our work has led us to conclude that the assessment of the conditional demands of beach handball players in competition must be done considering the specific playing positions.